1985
DOI: 10.1016/0014-5793(85)80160-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of atrial natriuretic factor receptors in dog kidney fractions

Abstract: Specific receptors for atria1 natriuretic factor were studied in purified glomeruli, proximal tubules, thick ascending limbs of Henle's loops and collecting ducts from dog kidney. Glomeruli contain the highest concentration of receptor sites (pK = 9.9, B,,,, = 200 fmol/mg protein), followed by collecting ducts (pK = 9.4, B mai = 150 fmol/mg). Low levels of receptor sites were also detectable in thick ascending limbs of Henle's loops (pK = 9.4, B,,, = 36 fmol/mg) while proximal tubules were completely devoid of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…The difference between WKY and SHR preceded the phase of established hypertension. Thus, the fold increase of glomerular cGMP levels by ANP was 8 and 33 for WKY and SHR, respectively, at 6 wk ofage, 11 (Fig. 3) bound to the ANP C-receptor (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The difference between WKY and SHR preceded the phase of established hypertension. Thus, the fold increase of glomerular cGMP levels by ANP was 8 and 33 for WKY and SHR, respectively, at 6 wk ofage, 11 (Fig. 3) bound to the ANP C-receptor (Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Despite numerous investigations of its renal mechanisms of action, the exact processes involved are still not fully understood. High concentrations of particulate guanylate cyclase and cGMP levels elevated by ANP have been noted in glomeruli (6)(7)(8)(9), which possess an abundance of specific ANP receptors (6,(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…This component of ANF's diuretic activity could be mediated via an inhibition of ADH secretion, which has been reported (45)(46)(47)(48), or via its tubular effect (49). Receptors for ANF have been described in various sections of the medulla (12,50). Our results indicate that such an anti-ADH action of ANF, whether or not related to the stimulation of particulate guanylate cyclase, is not reflected by urinary or plasma cGMP levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ANF apparently inhibits tubular sodium reabsorption, especially at the level of the medullary collecting duct (9-1 1). Although no receptors have been found on proximal tubules (12,13), lithium excretion is reported to be increased, suggesting either decreased reabsorption in the proximal tubules (14) or an effect secondary to hemodynamic changes.…”
Section: Introductionmentioning
confidence: 99%
“…Its natriuretic and diuretic activities are mediated by interaction with specific renal receptors. Previous studies demonstrated that two distinct receptor types are present in kidney, a high-affinity binding site (B recep tor) and a low-affinity binding site (C receptor) (7,21). It has been suggested that the Β receptor, which is tightly coupled to particulate guanylate cyclase, acts as the biologically active receptor (5), whereas C receptors seem to function as a hormonal buffer system by modulating plasma concentrations of ANF (2).…”
Section: Mcenroe and Alexander L Gerbesmentioning
confidence: 99%